Preparation and Characterization of Sb2Te3 Thin Films by Coevaporation. (12th July 2010) - Lv, Bin; Hu, Songbai; Li, Wei; Di, Xia; Feng, Lianghuan; Zhang, Jingquan; Wu, Lili; Cai, Yaping; Li, Bing; Lei, Zhi
Abstract : Deposition ofSb 2 Te 3 thin films on soda-lime glass substrates by coevaporation of Sb and Te is described in this paper.Sb 2 Te 3 thin films were characterized by x-ray diffraction (XRD), x-ray fluorescence (XRF), atomic force microscopy (AFM), x-ray photoelectron spectroscopy (XPS), electrical conductivity measurements, and Hall measurements. The abnormal electrical transport behavior occurred from in situ electrical conductivity measurements. The results indicate that as-grownSb 2 Te 3 thin films are amorphous and undergo an amorphous-crystalline transition after annealing, and the posttreatment can effectively promote the formation of Sb-Te bond and prevent oxidation of thin film surface.